SMES Sustainable Performance: A Conceptual Framework on The Moderating Role of Government Support - Nurfauzan, Muhammad Iqbal; Kuncoro, Engkos A.; Simamora, Bachtiar H.; Bandur, Agustinus (Journal of Cultural Analysis and Social Change, 2025)
This study investigates the role of digital capability in enhancing SMEs’ sustainable performance and the moderating effect of government support. Grounded in the Dynamic Capabilities Theory, Public Policy Theory, and the Triple Bottom Line framework, the paper proposes a conceptual model that integrates internal digital competencies with external institutional support to explain sustainability outcomes. A conceptual approach is employed and complemented by a pilot empirical test using survey data from 70 SME owners analyzed through Partial Least Squares Structural Equation Modeling (SEM-PLS). The measurement model demonstrates satisfactory reliability and validity, and the structural model provides preliminary evidence that digital capability positively influences sustainable performance, while government support strengthens this relationship. These findings offer theoretical contributions by bridging digital capability and institutional perspectives in the sustainability discourse, and practical implications by emphasizing the need for SMEs to develop robust digital competencies while leveraging supportive policies. Policymakers are encouraged to design interventions that reduce structural barriers and amplify the impact of digitalization on sustainability. Although limited by the pilot nature of the empirical test, the study provides a foundation for future research to validate and extend the proposed framework using larger and more diverse samples.